Meanings of Mobility : Family, Education, and Immigration in the Lives of Latino Youth - Schmalzbauer, Leah (Book collections on Project MUSE., 2023)
"How do low-income Latino youth experience educational mobility? How do they understand it in relation to social mobility more generally? And what does their educational mobility mean in the context of their socially marginalized families and communities? Meanings of Mobility explores these questions. It centers on the life histories of sixty low-income Latino youth, most of whom are the first in their immigrant families to go to college in the United States, and all of whom have now graduated or are set to graduate from Amherst College, one of the most selective private colleges in the United States. Over the past twenty years, shifts in the admissions policies of highly selective schools like Amherst, in partnership with privately funded recruitment initiatives, have reshaped the race and class composition of the U.S. educational elite. Although Latinos continue to be underrepresented in elite colleges and universities, their numbers are robust compared to years past. Yet, we know little about this new Latino demographic. Shifting away from a deficit-based focus on those Latino youth who do not make it to or through college, Schmalzbauer focuses instead on those who have made it, with the dual goal of bringing attention to and complicating the understanding of their educational success. The author seeks to better comprehend what factors have helped them succeed and what further supports they need"--